Stosowanie systemów zarządzania jakością a konkurencyjność przedsiębiorstw przemysłu spożywczego - Morkis, Grażyna (Applying the Quality Management Systems and Competitiveness in the Food Industry Enterprises, 2006)
If the Polish food industry enterprises want to be competitive on the national markets as well as on the European Union's markets, they have to offer safe food with high quality, which can meet constantly rising customer's requirements. To achieve it, is necessary to apply modem quality management systems in enterprises. Since Poland joined European Union the community has had significant influence on the implementation of obligatory managing systems in food industry by our country. Since 1st May 2004 to 1st May 2005 the number of food industry enterprises which applied and implemented modern quality systems rose significantly. Those systems had positive influence on the competitiveness level of Polish food enterprises.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 2, s. 137-142